Tabiat hubungan kadar faedah, volum dagangan dan pulangan sebelum dan selepas kejatuhan pasaran tahun 1997 di Bursa Saham Kuala Lumpur - Zaidi Isa,; Rubayah Yakob, (Penerbit Universiti Kebangsaan Malaysia, 2001)
Many researchers have tried to prove the relationship between volume, stock return and interest rates. Knowledge regarding the relationship between these three variables are important for investors, since the information obtained would guide them in their investment strategies whenever there are changes in these variables. In this study, the asymmetrical relationship between stock return and volume was examined and the influence of interest rates on volume was investigated. The results obtained proved the existence of the asymmetrical relationship between volume and stock return, in which positive returns had more effect on volume compared to negative returns. In addition, volume was also found to be significantly influenced by interest rates, while the direction of the relationship would depend on the economic situation, i.e before and after economic downturn